Understanding how financial knowledge influences the financial behavior of millennials in Ecuador - María Mercedes Baño Hifóng; Christian Ronny Mendoza Villavicencio; Patricia María Salazar Torres (Revista Venezolana de Gerencia)
Millennials in Ecuador, numbering approximately 3.9 million people, representing 23.2% of the population, face unusual final challenges. The economic and social circumstances of the country, together with the development of digitalization, have had an impact on the monetary habits of the generation. Young people must combine consumption, savings, and debt in an environment where financial education is not available to everyone. The objective of the study is to evaluate the influence of financial knowledge on the financial behavior of millennials in Ecuador acknowledgments aspects that address (a) savings, (b) consumption, (c) indebtedness and (d) investment of the target group. The methodology was proposed with a quantitative, non-experimental cross-sectional approach using a stratified convenience sampling, gathering information in three of the main provinces of Ecuador (Guayas; Azuay and Manabí); with the use of validated questionnaires that allowed to identify significant relationships between the dimensions of knowledge and financial behavior. The results show that the Theory of Bounded Rationality (Simon, 2000) is a predictive model to show the relationships between financial knowledge in its subjective dimension and the constructs of financial knowledge, thus contributing with new variables that condition financial behavior millennial in Ecuador.